Inhibition of MMP-3 activity and invasion of the MDA-MB-231 human invasive breast carcinoma cell line by bioflavonoids - Phromnoi K. (2014)
Aim: Stromelysin 1 (matrix metalloproteinase 3; MMP-3) is an enzyme known to be involved in tumor invasion and metastasis. In this study, flavonoids from vegetables and fruits, such as quercetin, kaempferol, genistein, genistin, and daidzein, were tested for their ability to modulate the secretion and activity of MMP-3 in the MDA-MB-231 breast cancer cell line. In addition, we investigated the in vitro effects of flavonoids on MDA-MB-231 cell invasion. Methods: The toxic concentration range of flavonoids was evaluated using the MTT assay. The ability of MDA-MB-231 cells to invade was evaluated using a modified Boyden chamber system. The activity of MMP-3 was determined by casein zymography. The secretion of MMP-3 was evaluated using Western blotting, casein zymography and confirmed by ELISA. Results: Some putative flavonoids, ie, quercetin and kaempferol (flavonols), significantly inhibited the in vitro invasion of MDA-MB-231 cells in a concentration-dependent manner, with IC50 values of 27 and 30 μmol/L, respectively. Quercetin and kaempferol also reduced MMP-3 activity in a dose-dependent manner, with IC50 values in the range of 30 μmol/L and 45 μmol/L, respectively. None of the flavonoids had a significant effect on the secretion of MMP-3. Conclusion: These data show that the flavonols quercetin and kaempferol have higher anti-invasion potency and higher MMP-3 inhibitory activity than isoflavones genistein, genistin and daidzein. In contrast, neither flavonols nor isoflavones have any effect on MMP-3 secretion. © 2009 CPS and SIMM All rights reserved.